Measurement of the ZZ production cross section in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Colombo, Tommaso; Consorti, Valerio; Davygora, Yuriy; Djuvsland, Julia Isabell; Dunford, Monica; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (Physical review letters, 2016)
The ZZ production cross section in proton-proton collisions at 13 TeV center-of-mass energy is measured using 3.2 fb−1 of data recorded with the ATLAS detector at the Large Hadron Collider. The considered Z boson candidates decay to an electron or muon pair of mass 66-116 GeV. The cross section is measured in a fiducial phase space reflecting the detector acceptance. It is also extrapolated to a total phase space for Z bosons in the same mass range and of all decay modes, giving 16.7+2.2−2.0(stat)+0.9−0.7(syst)+1.0−0.7(lumi) pb. The results agree with standard model predictions.